Resources
Testimonials
Plans
Sign in
Sign up
Resources
Testimonials
Plans
AI tutor
Welcome to Bytelearn!
Let’s check out your problem:
Evaluate the expression for
s
=
−
5
s = -5
s
=
−
5
.
\newline
Write your answer as a decimal or
whole number
.
\newline
4.6
−
s
=
4.6 - s =
4.6
−
s
=
_____
View step-by-step help
Home
Math Problems
Algebra 2
Evaluate variable expressions involving rational numbers
Full solution
Q.
Evaluate the expression for
s
=
−
5
s = -5
s
=
−
5
.
\newline
Write your answer as a decimal or whole number.
\newline
4.6
−
s
=
4.6 - s =
4.6
−
s
=
_____
Identify Expression:
Identify the expression to be evaluated.
\newline
We need to evaluate the expression
4.6
−
s
4.6 − s
4.6−
s
for
s
=
–
5
s = –5
s
=
–5
.
Substitute Value:
Substitute the value of
s
s
s
into the expression.
\newline
Substitute
s
=
−
5
s = -5
s
=
−
5
into the expression
4.6
−
s
4.6 - s
4.6
−
s
to get
4.6
−
(
−
5
)
4.6 - (-5)
4.6
−
(
−
5
)
.
Simplify Expression:
Simplify the expression.
4.6
−
(
−
5
)
4.6 - (-5)
4.6
−
(
−
5
)
becomes
4.6
+
5
4.6 + 5
4.6
+
5
because subtracting a negative is the same as adding a positive.
Perform Addition:
Perform the addition.
4.6
+
5
4.6 + 5
4.6
+
5
equals
9.6
9.6
9.6
.
More problems from Evaluate variable expressions involving rational numbers
Question
Combine the like terms to create an equivalent expression:
\newline
2
s
+
(
−
4
s
)
=
0
2s+(-4s)=\boxed{\phantom{0}}
2
s
+
(
−
4
s
)
=
0
Get tutor help
Posted 1 year ago
Question
Combine the like terms to create an equivalent expression:
\newline
−
4
p
+
(
−
6
p
)
=
□
-4p+(-6p)=\square
−
4
p
+
(
−
6
p
)
=
□
Get tutor help
Posted 1 year ago
Question
Combine the like terms to create an equivalent expression:
\newline
4
z
−
(
−
3
z
)
=
□
4z-(-3z)=\square
4
z
−
(
−
3
z
)
=
□
Get tutor help
Posted 1 year ago
Question
Combine the like terms to create an equivalent expression:
\newline
r
+
(
−
5
r
)
=
0
r+(-5r)=\boxed{\phantom{0}}
r
+
(
−
5
r
)
=
0
Get tutor help
Posted 1 year ago
Question
Combine the like terms to create an equivalent expression:
\newline
−
4
p
+
(
−
2
)
+
2
p
+
3
=
-4p+(-2)+2p+3=
−
4
p
+
(
−
2
)
+
2
p
+
3
=
Get tutor help
Posted 1 year ago
Question
Rewrite the expression in the form
k
⋅
z
n
k \cdot z^{n}
k
⋅
z
n
.
\newline
Write the exponent as an integer, fraction, or an exact decimal (not a mixed number).
\newline
3
z
4
⋅
3
z
3
4
=
3 \sqrt[4]{z} \cdot 3 z^{\frac{3}{4}}=
3
4
z
⋅
3
z
4
3
=
Get tutor help
Posted 1 year ago
Question
Let
y
=
3
x
y=3^{x}
y
=
3
x
.
\newline
Find
d
2
y
d
x
2
\frac{d^{2} y}{d x^{2}}
d
x
2
d
2
y
\newline
d
2
y
d
x
2
=
\frac{d^{2} y}{d x^{2}}=
d
x
2
d
2
y
=
Get tutor help
Posted 1 year ago
Question
Let
y
=
4
x
2
+
3
x
2
x
−
7
y=\frac{4 x^{2}+3 x}{2 x-7}
y
=
2
x
−
7
4
x
2
+
3
x
.
\newline
d
y
d
x
=
\frac{d y}{d x}=
d
x
d
y
=
Get tutor help
Posted 1 year ago
Question
d
d
x
(
e
x
cos
(
x
)
)
=
\frac{d}{d x}\left(\frac{e^{x}}{\cos (x)}\right)=
d
x
d
(
c
o
s
(
x
)
e
x
)
=
Get tutor help
Posted 9 months ago
Question
Let
f
(
x
)
=
1
x
2
f(x)=\frac{1}{x^{2}}
f
(
x
)
=
x
2
1
.
\newline
f
′
(
5
)
=
f^{\prime}(5)=
f
′
(
5
)
=
Get tutor help
Posted 1 year ago
Related topics
Algebra - Order of Operations
Algebra - Distributive Property
`X` and `Y` Axes
Geometry - Scalene Triangle
Common Multiple
Geometry - Quadrant